(3TQM aQGFV GdeNJUQ GdfGaYs - (3eLghds ((3YWGA Hf Ydj Gdbejs)
(3ChdgG (B:s
(3ChdgG(B: (3CeG HYO MeO Gddg QH GdYGdejf (B... (3abO CedjJ dcJGH GdehGQjK ef cJGH GdfGaY GdefJNH aj GdTQGFY cdeGJ JLQj dg eLQi GdTQM (B... (3cJGH GdehGQjK, GYde Cf GdehGQjK GYe ef GdaQGFV dCfgG JYe GdhQGKI HGdaQV hHGdbQGHIs
(3BNQgG (B:s
(3BNQgG(B: (3GdJQOO Cfg de jhLO Ydjg Odjd ef QhGjI Ch JfRjd abO CaJi GdTjNGf hGdSdGQjI (B.. (3GdJQOO CfgeG GHJOGA eYG acja jSJOd HGdGfbWGY Ydi JYjjf CUd GdCeQjf hdG jSJOd HGjJOGAgeG eYG Ydi Cfg eTcd GdCeQ hGdJQOO (B.. (3VYas
(3JHUQI GdeDda (B:s
(3jfSH aj HYV GdfSN ddeMbb Ydj Hf GdMSjf GdcQcjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B13: 230s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis